Co-transforming bar and CsALDH Genes Enhanced Resistance to Herbicide and Drought and Salt Stress in Transgenic Alfalfa (Medicago sativa L.) - Duan, Zhen; Zhang, Daiyu; Zhang, Jianquan; Di, Hongyan; Wu, Fan; Hu, Xiaowen; Meng, Xuanchen; Luo, Kai; Zhang, Jiyu; Wang, Yanrong (Frontiers in Plant Science, 2015)
Drought and high salinity are two major abiotic factors that restrict the productivity of alfalfa. By application of the Agrobacterium-mediated transformation method, an oxidative responsive gene, CsALDH12A1, from the desert grass Cleistogenes songorica together with the bar gene associated with herbicide resistance, were co-transformed into alfalfa (Medicago sativa L.). From the all 90 transformants, 16 were positive as screened by spraying 1 mL L-1 10% Basta solution and molecularly diagnosis using PCR. Real-time PCR analysis indicated that drought and salt stress induced high CsALDH expression in the leaves of the transgenic plants. The CsALDH expression levels under drought (15 d) and salt stress (200 mM NaCl) were 6.11 and 6.87 times higher than in the control plants, respectively. In comparison to the WT plants, no abnormal phenotypes were observed among the transgenic plants, which showed significant enhancement of tolerance to 15 d of drought and 10 d of salinity treatment. Evaluation of the physiological and biochemical indices during drought and salt stress of the transgenic plants revealed relatively lower Na+ content and higher K+ content in the leaves relative to the WT plants, a reduction of toxic on effects and maintenance of osmotic adjustment. In addition, the transgenic plants could maintain a higher relative water content level, higher shoot biomass, fewer changes in the photosystem, decreased membrane injury, and a lower level of osmotic stress. These results indicate that the co-expression of the introduced bar and CsALDH genes enhanced the herbicide, drought and salt tolerance of alfalfa and therefore can potentially be used as a novel genetic resource for the future breeding programs to develop new cultivars.